Scaling Effects on LLaMA Language Understanding Across GLUE and SuperGLUE Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: What is the impact of model scaling (e.g., 7B vs. 70B parameters) on LLaMA's language understanding capabilities as measured by GLUE or SuperGLUE benchmarks. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.7/10. This report is a machine-generated literature synthesi
Machine-generated literature synthesis.